Genetic parameter estimates and selection gain for multiple traits in white Guinea yam (Dioscorea rotundata) in Ghana - Darkwa, K.; Adjei, E.A.; Chamba, E.B.; Sayibu, A.; Amegbor, I.K.; Agyapong, F.A.; Sayibu, Z.; Sayibu, I.; Kangmennaang, M.; Issifu, M.; Agre, P.A.; Adebola, P.; et al. (2025)
Quantifying selection gains enables a more targeted assessment of breeding program effectiveness, highlighting opportunities for strategic improvement and optimized genetic advancement in white Guinea Yam. This study assessed genetic parameters and gain for key traits in a white Guinea yam (D. rotundata) breeding population. A total of 81 genotypes were evaluated for two seasons using a 9 × 9 lattice design with three replicates. Data was collected on yam mosaic virus disease severity, tuber yield and tuber dry content for genetic analysis. Broad sense heritability was generally high (> 60) for most of the traits. At the same time, the corresponding genetic advance as a percentage of the mean was exceptionally high (30.28–93.96%) for tuber yield, tuber flesh oxidation, average tuber weight and number of tubers per plant, suggesting additive genetic effects. A multi-trait selection index of the 5% highest performing genotypes revealed positive genetic gain for plant vigour, tuber length, and width, tuber weight per plant, average tuber weight and fresh tuber yield. The genetic gain was, however, negative for tuber dry matter content compared to the check varieties, necessitating a modification of the current breeding scheme such that post-harvest food quality is not sacrificed for tuber yield. Ranking of the breeding lines based on the multi-trait selection index identified four lines (TDr1700004_014, TDr1700004_113, TDr1700001_112 and TDr1700002_090) with high genetic merits for all the economic traits. These lines can be used as potential trait progenitors and evaluated further for possible release as new varieties. Our results decipher the genetic control and provide an overview of the performance of the breeding program for key traits in white Guinea yam.